Effects of typical corn kernel shapes on the forming of repose angle by DEM simulation - Shi, Linrong; Zhao, Wuyun; Yang, Xiaoping (International Journal of Agricultural and Biological Engineering, 2022)
Corn kernel shape is an important feature to improve the accuracy of simulation results, also the repose angle is often used to calibrate model parameters in simulation. In this study, the effects of the corn kernel shapes on the behavior during corn kernels accumulation were investigated in detail. Firstly, the DEM models of three typical shapes of corn kernels were developed. Secondly, the influences of the corn kernel shapes on the process of forming repose angle were investigated, such as corn kernels distance change, energy conversion, and the contact number between corn kernels. Results show that the corn kernel shape has a significant effect on the repose angle formation. The irregular shape of corn kernels limit their rolling when adding the corn kernel length in one or two directions. In addition, the irregular shapes of corn kernels increase the contact number and extend simulation time. Regular shape corn kernels need to be mixed with irregular shape corn kernels to improve their flowability. Finally, observation of the trajectory of corn kernel repose angles indicates that spherical corn kernels contact the bottom plate early, and forming small cone first, then the cone becomes bigger to change the direction of other corn kernels from top to bottom.Keywords: corn kernel shape, energy conversion, repose angle, DEMDOI: 10.25165/j.ijabe.20221502.5670Citation: Shi L R, Zhao W Y, Yang X P. Effects of typical corn kernel shapes on the forming of repose angle by DEM simulation. Int J Agric & Biol Eng, 2022; 15(2): 248–255.